Women with type 1 diabetes and women with type 2 diabetes differ in knowledge and beliefs about contraception and pregnancy. Issue 4 (2nd February 2021) - Hendrieckx, Christel; Morrison, Melinda; Audehm, Ralph; Barry, Alison; Farrell, Kaye; Houvardas, Effie; Nankervis, Alison; Porter, Cynthia; Scibilia, Renza; Ross, Glynis
Abstract: Aims: To assess differences in knowledge and beliefs about pregnancy in women with diabetes. Methods: Questions were from the Australian ' Contraception, Pregnancy & Women's Health' survey. Women (18–50 years) were eligible if pregnant or planning pregnancy. Knowledge and beliefs items were adapted from the Reproductive Health and Behaviours Questionnaire. Results: Compared to women with type 2 diabetes ( n  = 103), women with type 1 diabetes ( n  = 526) had higher scores for knowledge about pregnancy in diabetes (type 1 diabetes 9.8 ± 2.4 vs. type 2 diabetes 7.7 ± 3.1), beliefs about benefits (type 1 diabetes 18.4 ± 2.2 vs. type 2 diabetes 17.2 ± 3.3), cues‐to‐action (type 1 diabetes 2.7 ± 1.4 vs. type 2 diabetes 1.5 ± 1.3) and self‐efficacy (type 1 diabetes 22.6 ± 5.5 vs. type 2 diabetes 20.2 ± 6.1 (all p  < 0.001) regarding preparing for pregnancy. Major knowledge gaps were the need for higher dose folate compared to women without diabetes and uncertainty about breastfeeding recommendations. Women with type 1 diabetes believed more strongly in the benefits of 'close to target' glucose levels prior to pregnancy and using contraception to prevent unplanned pregnancy; they also felt more confident to access pre‐pregnancy care and to wait for optimal glycaemia before pregnancy. Women with type 2 diabetes were less aware of contraceptive choices, and risks associated with hyperglycaemia before or early in pregnancy. Conclusions: The findings highlighted main gaps in knowledge and beliefs about planning for pregnancy. Especially in type 2 diabetes, there is a need for evidence‐based messaging and strategies addressing these gaps, to raise understanding to prepare for future pregnancies.